Bacteria elevate extracellular adenosine to exploit host signaling for blood-brain barrier disruption. Issue 1 (31st December 2020) - Zhao, Zunquan; Shang, Xueyi; Chen, Ying; Zheng, Yuling; Huang, Wenhua; Jiang, Hua; Lv, Qingyu; Kong, Decong; Jiang, Yongqiang; Liu, Peng
ABSTRACT: Bacterial meningitis remains a substantial cause of mortality worldwide and survivors may have severe lifelong disability. Although we know that meningeal bacterial pathogens must cross blood-central nervous system (CNS) barriers, the mechanisms which facilitate the virulence of these pathogens are poorly understood. Here, we show that adenosine from a surface enzyme (Ssads) of Streptococcus suis facilitates this pathogen's entry into mouse brains. Monolayer translocation assays (from the human cerebrovascular endothelium) and experiments using diverse inhibitors and agonists together demonstrate that activation of the A1 adenosine receptor signaling cascade in hosts, as well as attendant cytoskeleton remodeling, promote S. suis penetration across blood-CNS barriers. Importantly, our additional findings showing that Ssads orthologs from other bacterial species also promote their translocation across barriers suggest that exploitation of A1 AR signaling may be a general mechanism of bacterial virulence.